Platform Merdeka Mengajar: Tantangan dan Hambatan Guru di SMA IT Izzatuna - Alfionita, Ochi; Apriani, Esi; Reta, Nita Elva (Journal of Innovation in Teaching and Instructional Media, 2025)
The Merdeka Mengajar Platform is an innovation by the Ministry of Education and Culture aimed at assisting teachers in teaching according to students' abilities, providing training to enhance competence, and creating work to inspire colleagues. This research aims to analyze the challenges and obstacles faced by teachers at SMA IT Izzatuna in using the Merdeka Mengajar Platform. This platform is part of the Merdeka Belajar policy, which is expected to help teachers improve the quality of teaching and access to educational resources. However, in its implementation, several challenges arise, including limited technological facilities, lack of training, and varying levels of digital literacy among teachers. This research employs a qualitative method with in-depth interviews as the data collection technique, involving teachers at SMA IT Izzatuna as the main respondents. The results indicate that while the Merdeka Mengajar Platform offers benefits in terms of flexibility and accessibility of learning materials, technical obstacles and the lack of training support are significant barriers. Therefore, further efforts are needed from both schools and the government to overcome these challenges so that the platform can be used optimally.